COMPARATIVE STUDY OF ACCOUNT OPENING PROCESS IN BANK SULUTGO AND BANK MANDIRI: STAKEHOLDERS PERSPERCTIVE - Christian, Yeyen Apriana; Worang, Frederik G. (Universitas Sam Ratulangi, 2018)
Abstract: Account opening is a first step for customers to join a bank. Customer service as a service provider in account opening process is responsible for the convenience of customers in service. The purpose of this research is to analyze the perspectives of stakeholders, in this case customer and customer service toward the account opening process. Three attributes that become a benchmark in this study are service marketing, technology and standard operating procedures. Researcher using qualitative study to processed data. Researcher has interviewed 30 informants for gathering data which are 20 customers who have opened account in Bank SulutGo and Bank Mandiri, 5 customer services of Bank SulutGo and 5 customer services Bank Mandiri. Based on the result, it shows that customer services give the best of their service in account opening but it lack of attention in their attitude in daily transactions. Customers suggest Bank SulutGo and Bank Mandiri to provide account opening via online. Standar operating procedure in Bank SulutGo and Bank Mandiri is similar. In account opening, customer services should ensure to really understand the needs of customers and approach the customers to enjoy the account opening process.Keywords: account opening process, service process